No city on the horizon: Autonomous cars, artificial intelligence, and the absence of urbanism - McCarroll, Cian; Cugurullo, Federico (Frontiers in Sustainable Cities, 2022)
In this perspective piece we use a case study of Phoenix (Arizona) to explore the ways in which the implementation of autonomous vehicle technology is tied to the political economy of the city. We highlight the potential urban benefits that can stem from the use of autonomous vehicles, while also bringing to the fore the necessity of governance in realizing these same benefits. By using Phoenix as a case study, we illustrate the dissonance that exists between policymakers within government and the future urban imaginaries that are used as reasons to justify Phoenix as a test ground. By viewing the position of stakeholders within industry and within government we address the individual and political gains that adoption of such technology can bring on an inter-state competitive level. These dynamics of market competition, combined with a lack of proactive engagement in urban planning show that the potential urban benefits that can be brought on by the autonomous vehicle are left solely to the imagination.